BEHAVIORAL INTENTION AND USE BEHAVIOR ANALYSIS OF DANA FINTECH USERS USING THE UTAUT 2 METHOD - Komang Putri Damayanti; Sephy Lavianto; I Gst. Agung Pramesti Dwi Putri (Jurnal TAM (Technology Acceptance Model), 2022)
DANA Fintech is currently used for non-cash transactions due to the convenience and practicality of transactions offered by service providers. However, it is currently unknown to what extent the success of the electronic wallet has been implemented and there are still problems such as loss of balance, failure to top up balances and the features of the DANA application which are still poorly understood. One of the determining factors for the success of a system which is implemented is from the side of user acceptance, behavioral intention (user interest) and use behavior (user behavior). This study aimed to determine what factors could influence the Behavioral Intention and Use Behavior of DANA Fintech Users towards private workers in the city of Denpasar. This research was conducted using a quantitative approach, distributing online questionnaires, and analyzing data processing using SPSS version 25 and SmartPLS 3.0 software. The results of the 12 (twelve) hypotheses proposed, 7 (seven) hypotheses were declared insignificant and rejected because the T-statistical value of the hypothesis was less than 1.96, while 5 (five) hypotheses were declared significant and accepted because the T-statistical value of the hypothesis is more than 1.96. The results of this study are expected to be one of the considerations in making decisions for electronic wallet service providers to be implemented more optimally.